Designing effective feedback processes in higher education : a learning-focused approach - Winstone, Naomi E., ....-; Carless, David, ....- (London ; : Routledge, 2020)
"This book addresses the challenge of developing effective feedback processes in higher education, combining theory and practice to equip and empower educators. Including discussions on promoting student engagement with feedback, technology-enabled feedback, and effective peer feedback, this book analyses examples of feedback practice and illustrates them through practical examples and up-to date syntheses of relevant literature. It is a must-read for educators, researchers and academic developers in higher education, who will benefit from a guide to feedback research and practice that addresses well-recognized challenges in relation to assessment and feedback"--
Keywords: College teaching; Communication in higher education; Hoger onderwijs ; feedback